Effect of natural dyes onquality of catfish ball (pangasius hypophthalmus) During cold storage (± 50c) - Asmidar '; Syahrul '; Nur Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of study was to determine the effect of natural dyes on (floor, carrots, yeast) catfish balls during 0, 10, 20, 30, 40 days of storage at a cold temperature (± 5° C). Strorage is best at day 20. Catfish balls made from natural dyes with 10% for each concentration. The result was evaluate to and proximate analysis (content, protein content, ash content) in meatballs catfish is 10%. Were organoleptic (color, scent, texture, taste), and total bacteria (TPC) the result showed that fat content for each treatment was 0.21%, 3.71%, 3.25%, 3.93%; ash content of 2.64%, 5.62%, 6.26%, 8.00%; carbohydrate content of 13.70%, 9.77%, 12.79%, 11.61%, and total bacteria colony 2.05x105 cells/g, 1.68x10. The results showed that the meatballs natural dyes are given leaf value best results. The water content of 54.16%, 49.54%, 51.17%, 49.50%; protein content of 12.85%, 19.31%, 11.07%, 16.93%, total bacteria colony 2.05x105, 1.68x105, 1.75x105, 1.63x105 cells/g.Keywords: Meatballs, natural dyes, catfish.